LEGAL ANALYSIS OF THE INK PROCUREMENT PROJECT COLLABORATION AT THE GENERAL ELECTION COMMISSION REVIEWED BASED ON LAW NUMBER 5 OF 1999 CONCERNING THE PROHIBITION OF MONOPOLY PRACTICES AND UNFAIR BUSINESS COMPETITION - Latif, Abdul; Daryono, Julius Wahyu; Fitriah, Siti Nimah; Silalahi, Udin (Justisi: Jurnal Ilmu Hukum, 2025)
The procurement of fingerprint ink in the 2004 Election has become a serious concern due to indications of collusion in the tender process involving auction participants and KPU officials. This case reflects the complexity of violations that are not only related to business competition law as regulated in Article 22 of Law No. 5 of 1999, but also involve elements of corruption in accordance with Law No. 31 of 1999 in conjunction with Law No. 20 of 2001. This study uses a normative juridical method to analyze the form of collusion that occurred, its implications for the procurement system of goods and services, and coordination between KPPU and law enforcement officers in handling this case. The results of the study indicate that weak supervision and lack of synergy between institutions hamper the effectiveness of law enforcement, so that regulatory reform and increased transparency are needed to prevent similar practices in the future.